Eaching Learning Process Of Speaking To The Eight Grade Students At SMP N 2 Colomadu In 2011/ 2012 Academic Year - Lianisari, Epri (2012)
The research paper aims at describing the generally are teaching learning process of speaking and focused the objectives of the learning, the material of speaking, the teaching technique of speaking, the media in speaking, the procedure in teaching speaking activities, the evaluation, the problem faced by the teacher and the students. In this study, the writer employs a descriptive qualitative research which describes about the teaching learning process. The subject of this research is the eighth grade students of SMP N 2 Colomadu. The writer takes 8A class as the subject on the study. Then, the methods of collecting data are observation, document, and interview. And the techniques for analyzing data are reduction, display, and conclusion drawing. The results of the research show that: 1) the objectives of learning, 2) the material of speaking, 3) the teaching technique of speaking are role play, discussion, and dialogue, 4) the varieties of teaching media are as follows: pictures and images, board, computer, video, radio, and tape recorder, 5) the procedure in teaching speaking activities the writer finds that the classroom procedure uses three phases namely: exploration, elaboration, and confirmation. The activities in exploration are asking question, giving explanation, and giving example of the text, in elaboration, the activities is makes a group and confirmation activities are giving explain material clearly in every meeting and giving the task as homework, 6) The evaluation, 7) problems faced by the teacher are managing the time, classroom management, and the students' capability, 8) the problems faced by the students in speaking are limited vocabulary, pronunciation, grammar, and anxiety in the process.